Chronobiome medicine: circadian regulation of host–microbiota crosstalk in systemic physiology - Bautista, Jhommara; López-Cortés, Andrés (Frontiers in Endocrinology, 2025)
Circadian rhythms, governed by central and peripheral clocks, orchestrate nearly all aspects of human physiology, including metabolism, endocrine function, neuroimmune activity, and behavior. Emerging evidence reveals that these oscillations are closely intertwined with the gut microbiota, which itself displays diurnal fluctuations in composition and metabolite production. This bidirectional regulation establishes a dynamic circadian–microbiota axis that synchronizes nutrient processing, hormonal secretion, immune surveillance, and neural signaling. Disruption of this temporal alignment, through genetic, environmental, or lifestyle factors, precipitates systemic dysregulation, fostering metabolic syndrome, endocrine imbalance, immune dysfunction, neuropsychiatric vulnerability, cardiovascular alterations, and carcinogenesis. Mechanistic studies highlight that microbial-derived metabolites such as short-chain fatty acids, bile acids, and indoles act as circadian cues, while host clock genes modulate microbial ecology and intestinal barrier integrity. These insights underscore the translational potential of circadian precision medicine, in which time-restricted feeding, probiotics, prebiotics, and chronotherapy restore synchrony between microbial and host clocks. This review synthesizes current knowledge on circadian modulation of microbiota-mediated crosstalk across metabolic, neural, immune, and endocrine pathways, emphasizing its implications for health, disease, and novel therapeutic strategies.